Crocetin reduces TNBS-induced experimental colitis in mice by downregulation of NFkB - Kazi Hamid; Qian Zhiyu (The Saudi Journal of Gastroenterology, 2009)
Background/Aim: Ulcerative colitis (UC) is characterized by oxidative and nitrosative stress, leukocyte infiltration and upregulation of proinflammatory cytokines. In this study, we aim to investigate the effects of crocetin and its protective mechanism on 2,4,6- trinitrobenzene sulfonic acid (TNBS)-induced colitis in mice model. Materials and Methods: Intestinal lesions (judged by macroscopic and histological score) were associated with neutrophil infiltration (measured as increase in myeloperoxidase (MPO) activity in the mucosa), and high levels of malondialdehyde MDA (an indicator of lipid peroxidation). Results: Dose-response studies revealed that treatment of mice with crocetin (50 mg/kg/day) i.g. for 8 days) significantly ameliorated diarrhea and the disruption of colonic architecture. Higher and lower doses (100 and 25 mg/kg/day) did not exhibit comparable effects. In crocetin-treated mice, a significant reduction was noted in the degree of both neutrophil infiltration (measured as decrease in myeloperoxidase activity) and lipid peroxidation (measured as decrease in malondialdehyde activity) in the inflamed colon. Crocetin also reduced the levels of nitric oxide (NO) associated with the favorable expression of TH1 and TH2 cytokines and inducible NO synthase along with the down regulation of nuclear factor-kB (NFkB). Conclusion: These findings suggest that crocetin exerts beneficial effects in experimental colitis, and therefore we propose that this carotenoid may have therapeutic implications for human UC and can be administered along with the conventional therapy of UC